High prevalence and different genotypes of Crimean-Congo hemorrhagic fever virus genome in questing unfed adult Hyalomma marginatum in Thrace, Turkey - GARGILI KELEŞ, AYŞEN; AKYILDIZ, GÜRKAN (ELSEVIER GMBH, 2021)
Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne viral disease in the old continents, in many countries south of the 50 degrees North Parallel. The agent is known to be the most prevalent and major cause of severe and fatal human hemorrhagic diseases among the tick-borne viruses, and is the second most widespread of all medically critical arboviruses following dengue. Members of the Hyalomma genus are mainly involved in the natural transmission of the CCHF virus (CCHFV); of those, H. marginatum is known to be the primary vector of the disease in the Western Palaearctic. In general, epidemiological studies have been based on serological detections in the hosts and/or virus screening of ticks collected from the hosts. To the best of our knowledge, only a few studies have been carried out to screen the virus in unfed, questing field ticks. Nevertheless, detection of the virus in questing ticks is known to be a crucial parameter to determine the possible vector roles of the ticks and to understand the ecological dynamics of related diseases. In this study, 200 (75 males,125 females) questing H. marginatum adults collected from the field in nine villages in Thrace, located in the European part of Turkey, were screened individually for CCHFV using nested PCR. As a result, 103 (51.5 %) ticks were determined as positive with various strains of CCHFV. High positivity in questing vectors in a region where a significantly lower number of human cases have been encountered suggests that there should be some region-specific drivers that are effective in the natural dynamics of the disease. Detailed etiological and epidemiological studies are needed to reveal the possible reason for this unexpected discrepancy.
Keywords: Tick; Hyalomma marginatum; Crimean Congo hemorrhagic fever; Thrace; Turkey